Interworking of CRMA and ATM networks - Wang, Xiaoqun. (2009)
In wide area networks, the Asynchronous Transfer Mode (ATM) is emerging as an transport technology for the broadband networks. The main advantage of the ATM is that it provides flexible transmission and switching mechanism to accommodate a large variety of services. Though ATM can be used for LAN/MANs, at present it does not provide economical solution for LAN/MAN. A simple Cyclic-Reservation Multiple-Access (CRMA) protocol proposed in [1] can be used as a media access protocol for high-speed (giga bit per second) LAN and MAN on slotted unidirectional bus structure. While there is a need for interconnection of existing LAN/MAN with ATM networks, the evolution of new LAN/MAN protocol will depend on how easily and efficiently the protocol can interwork with the ATM.